2020
DOI: 10.1002/aic.17038
|View full text |Cite
|
Sign up to set email alerts
|

Power generation from waste heat: Ionic liquid‐based absorption cycle versus organic Rankine cycle

Abstract: Aspen Plus ® simulations using the Peng-Robinson (PR-EOS) and the COSMO-SAC models were performed to study absorption power cycles (APCs) using mixtures of R-134a with two ionic liquids, [C 2 C 1 im][Tf 2 N] or [C 6 C 1 im][Tf 2 N], and compared against an R-134a organic Rankine cycle (ORC) operating under similar conditions. The PR-EOS results were in agreement with calculations from a PR model fitted to the R-134a + IL experimental phase equilibrium data. The APCs have similar efficiencies and outperform the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The use of other refrigerants (water, R-134a, pentane, etc.) in IL-based absorption refrigeration cycles has also been reported in the literature. ,, Again, Yokozeki et al initially published the use of ILs in water absorption refrigeration cycles compared with the traditional water/[Li]­[Br] system and found that some water/IL pairs may compete with the reference, with the [emim]­[MePO 4 ] IL having the highest COP (0.691). The proper IL selection and optimization of the cycle’s operating variables enhanced the performance of the traditional water/[Li]­[Br] system.…”
Section: Key Applications Of Ionic Liquids Analyzed Using Process Sim...mentioning
confidence: 90%
See 4 more Smart Citations
“…The use of other refrigerants (water, R-134a, pentane, etc.) in IL-based absorption refrigeration cycles has also been reported in the literature. ,, Again, Yokozeki et al initially published the use of ILs in water absorption refrigeration cycles compared with the traditional water/[Li]­[Br] system and found that some water/IL pairs may compete with the reference, with the [emim]­[MePO 4 ] IL having the highest COP (0.691). The proper IL selection and optimization of the cycle’s operating variables enhanced the performance of the traditional water/[Li]­[Br] system.…”
Section: Key Applications Of Ionic Liquids Analyzed Using Process Sim...mentioning
confidence: 90%
“…46 NTf 2based ILs have also been evaluated for an R-134a system under different conditions and compared with the traditional organic Rankine cycle (ORC) for cooling production. 111 Without optimization, the ORC achieved better efficiencies than absorption refrigeration cycles using NTf 2 -based ILs. This was especially clear when operating with lower-grade heating sources.…”
Section: Absorption Refrigeration Cyclesmentioning
confidence: 98%
See 3 more Smart Citations